A butterfly-like lead-doped titanium-oxide compound with high performance in photocatalytic cycloaddition of CO2 to epoxide. Issue 8 (31st January 2023) - Said, Amir; Zhang, Guanyun; Liu, Caiyun; Wang, Dexin; Niu, Huihui; Liu, Yanshu; Chen, Guanjie; Tung, Chen-Ho; Wang, Yifeng
Abstract : A novel butterfly-like lead-doped titanium-oxide compound that showed high performance in photocatalytic cycloaddition of CO2 to epoxide under simulated solar irradiation is reported. Abstract : The cycloaddition reaction of CO2 to epoxides is quite promising for CO2 capture and storage as well as the production of value-added fine chemicals. Herein, a novel atomically precise lead-doped titanium-oxide cluster with the formula Ti10 Pb2 O16 (phen)4 (Ac)12 (DMF)2 (denoted as Ti10 Pb2 ; phen = 1, 10-phenanthroline; Ac = acetate; DMF = dimethylformamide) was synthesized through a facile solvothermal process, and is a molecular photocatalyst with surface-anchored main-group metal active sites. Its structure was characterized by single-crystal X-ray diffraction and other complementary techniques. Ti10 Pb2 showed high photo-response and charge-separation efficiency under simulated sunlight irradiation. Ti10 Pb2 was successfully used in the cycloaddition reaction of CO2 with epoxides under solvent-free conditions. While its catalytic activity due to the Lewis acidity was moderate, simulated solar light irradiation further enhanced the reaction rate, demonstrating the synergistic effect of photocatalysis and Lewis-acid thermocatalysis.